Metacognition in Auditory Distraction: How Expectations about Distractibility Influence the Irrelevant Sound Effect. Issue 1 (30th November 2017) - Röer, Jan Philipp; Rummel, Jan; Bell, Raoul; Buchner, Axel
Task-irrelevant, to-be-ignored sound disrupts serial short-term memory for visually presented items compared to a quiet control condition. We tested whether disruption by changing state irrelevant sound is modulated by expectations about the degree to which distractors would disrupt serial recall performance. The participants' expectations were manipulated by providing the (bogus) information that the irrelevant sound would be either easy or difficult to ignore. In Experiment 1, piano melodies were used as auditory distractors. Participants who expected the degree of disruption to be low made more errors in serial recall than participants who expected the degree of disruption to be high, independent of whether distractors were present or not. Although expectation had no effect on the magnitude of disruption, participants in the easy-to-ignore group reported after the experiment that they were less disrupted by the irrelevant sound than participants in the difficult-to-ignore group. In Experiment 2, spoken texts were used as auditory distractors. Expectations about the degree of disruption did not affect serial recall performance. Moreover, the subjective and objective distraction by irrelevant speech was similar in the easy-to-ignore group and in the difficult-to-ignore group. Thus, while metacognitive beliefs about whether the auditory distractors would be easy or difficult to ignore can have an effect on task engagement and subjective distractibility ratings, they do not seem to have an effect on the actual degree to which the auditory distractors disrupt serial recall performance.